MATERI PENDIDIKAN IBADAH / FIKIH DALAM HADITS - Anita Indria (El-Rusyd, 2016)
This study discusses the values of Islamic education in the tradition of worship / Jurisprudence include prayer, alms, fasting and pilgrimage. This research is to understand the literature discussed and analyzed so came the idea of the material worship / Jurisprudence which includes prayer, alms, fasting and pilgrimage contained in the hadith the prophet. Conclusions contained in the hadith of worship / fiqh that is the education that we can take.